1985
DOI: 10.1289/ehp.8560381
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent inhibition of development of GGT positive foci in rat liver by the environmental contaminant di(2-ethylhexyl) phthalate.

Abstract: The ability of di(2-ethylhexyl) phthalate (DEHP), a widely used plasticizer and environmental contaminant, to suppress development of putative preneoplastic lesions in rat liver was evaluated. y-Glutamyl transpeptidase-positive (GGT + ) foci were initiated in the livers of Sprague-Dawley male rats with a single dose of diethylnitrosamine (DEN) following partial hepatectomy. Promotion of foci was commenced by feeding a choline-deficient diet (CD). A group of control rats was fed a choline-supplemented diet (CS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…DEHP, which induces formation of peroxisomes, has been shown to be a hepatocarcinogen per se in rats when given in the diet at 0.6% or 1.2% (35). Earlier we had reported on the interaction of DEHP with DENAinitiated hepatocarcinogenic markers evaluated after only 10 weeks of exposure (5,6). In the present studies, expression of two putative markers of neoplasia in rat liver, GGT and GST-P, was used as probes to detect AT; and N. AF staining for GGT and GST-P is not found in livers of rats exposed to some peroxisome proliferators such as Wy-14,643, Br-91, and cibrofibrate (36,37).…”
Section: A Initiated + Phthalate Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…DEHP, which induces formation of peroxisomes, has been shown to be a hepatocarcinogen per se in rats when given in the diet at 0.6% or 1.2% (35). Earlier we had reported on the interaction of DEHP with DENAinitiated hepatocarcinogenic markers evaluated after only 10 weeks of exposure (5,6). In the present studies, expression of two putative markers of neoplasia in rat liver, GGT and GST-P, was used as probes to detect AT; and N. AF staining for GGT and GST-P is not found in livers of rats exposed to some peroxisome proliferators such as Wy-14,643, Br-91, and cibrofibrate (36,37).…”
Section: A Initiated + Phthalate Estersmentioning
confidence: 99%
“…Earlier experiments demonstrated that a 10-week exposure to di(2-ethylhexy1)phthalate (DEHP) significantly reduced the number of AF appearing in livers of rats previously initiated with a single dose of the liver carcinogen diethylnitrosamine (DENA) (5,6). Conversely, exposure of DENA-initiated animals to di-n-octylphthalate (DOP) for 10 weeks caused a fivefold increase in the number of foci compared with animals treated with DENA alone (6).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DEHP profoundly caused structural and functional properties of the liver. It affected the cell organelles, such as peroxisomes and mitochondria, and expression of the enzymes involving in fatty acid transport and β‐oxidation . The U.S. Environmental Protection Agency has defined plasticizes as water and air pollutants .…”
Section: Introductionmentioning
confidence: 99%